Meta-analysis of risk association between interleukin-17a gene polymorphism and chronic periodontitis - P K Sasikumar; Sheeja S Varghese; Thanga Kumaran; Sakthi Saranya Devi (Wolters Kluwer Medknow Publications, 2020)
The association of genetic polymorphisms with periodontitis has been studied extensively. The interleukin-7 (IL-17) is a group of cytokines, which comprises six different molecules (IL-17A, B, C, D, E, and F). Among this, IL-17A is the most commonly understood cytokine, and its polymorphism plays a critical role in inflammatory diseases and periodontal inflammation. The present study was aimed at pooling the data available for meta-analysis and to evaluate whether IL-17A (rs2275913) polymorphism is associated with the susceptibility of chronic periodontitis.